Measuring Heart Rate by Using the Contact Free Video Imaging on a Built-In Camera of a Smartphone - Bui, Khoa V.; Trinh, Duc Q.; Nguyen, Tung T.; Nguyen, Trung N. (Old Journal, 2019)
Digital camera is now becoming a very popular and useful clinical tool for measuring the human vital signs such as cardiac pulse, breath rate, or blood pressure through noncontact video recording with the signal extracted from objects such as blood vessel, head motion, or human arm, etc. In this paper, we explore the potential that the reliable heart rate can be measured remotely by the facial video recorded using smartphone camera. The accuracy of the estimated heart rate was evaluated by comparing with the heart rate measured directly from the reference digital electrocardiogram (ECG). We also present our preliminary results of the heart rates measured with different lighting conditions, spectral components, facial parts, and alcoholic volume.